DIPLOMASI PUBLIK BELIZE DALAM MENINGKATKAN WISATAWAN INTERNASIONAL DI MASA PANDEMI COVID-19 MELALUI TOURISM GOLD STANDARD 2020-2022 - Halida Azalea Iffa Dina (2023)
This research aims to investigate the role of Belize's public diplomacy in increasing the number of international tourists during the COVID-19 pandemic through the implementation of the Tourism Gold Standard program from 2020 to 2022. The pandemic has significantly impacted the tourism sector, including in Belize, where tourism contributes 44.7% to the country's Gross Domestic Product. This study adopts a qualitative approach, collecting data through interviews, observations, and document analysis to support the research process. The research adopts Joseph Nye's theory of Public Diplomacy, focusing on three key dimensions related to the study: international broadcasting, advocacy, and listening. Through the implementation of the Tourism Gold Standard program, Belize has prioritized health aspects and COVID-19 prevention measures in tourism facilities and transportation. Belize's public diplomacy efforts have effectively disseminated information about the safety of tourism in Belize during the pandemic through successful campaigns. The findings of the research indicate that through effective public diplomacy efforts, Belize has managed to revive its tourism sector, which experienced a decline due to the COVID-19 pandemic. Through effective public diplomacy, Belize has built an image as a safe tourism destination amidst the pandemic. Therefore, this research provides an overview of Belize's public diplomacy efforts in revitalizing the tourism sector amid the COVID-19 pandemic through the implementation of the Tourism Gold Standard program. The findings of this research can offer insights and recommendations for other countries facing similar challenges in developing their tourism sectors during the pandemic.